Comparative aspects of the diet of anuran amphibians at different elevations on Gunung Jagoi, Sarawak, Borneo - Nuraishah, Bt Abdul Rahman (Faculty of Resource Science and Technology, 2012)
Feeding habit and food preference of the anuran amphibian at different elevation of Gunung Jagoi were studied from 8 to 11 November 2011 and 2 to 5 February 2012. The sampling was conducted of the 100 m streams transect between the elevation of 60 m (Kg Serasot) and 240 m (Kg Bung Jagoi) above sea level. A total of 15 species were captured in Kg Serasot and 10 species in Kg Bung Jagoi. There was a significant difference between the anuran diversity in Kg Serasot and Kg Bung Jagoi (p<0.05, Zar t-test). The regurgitated stomach content of 25 species were analysed and it shows that arthropods comprise most diet. The relationship between the diet of frogs with their potential prey available in the environment were done and it is determined that Megophrys nasuta, Limnonectes kuhlii, and Limnonectes malesianus were assumed to be generalist feeder. Frogs like Limnonectes leporinus, Leptolalax gracilis, Leptobraehella mjobergi, Hylarana ranieeps, Hylarana plett/rata and Mierohyla perpava were classified to be a specialist feeder.